Patient satisfaction and health services in two public hospitals in Mogadishu, Somalia: a cross-sectional study - Abdifatah Abdullahi Jalei; Yahye Sheikh Abdulle Hassan; Abdifetah Ibrahim Omar; Abdifetah Ibrahim Omar; Mohamed Abdi Ali (Frontiers in Health Services, 2025)
IntroductionHealthcare system performance widely recognizes patient satisfaction as a pivotal measure that directly influences both the quality of care and health outcomes. It reflects patients’ experiences and perceptions of healthcare delivery, which are essential for identifying gaps and implementing improvements in health services. In conflict-affected regions like Somalia, understanding the factors that shape patient satisfaction is crucial for optimizing healthcare delivery and building trust between healthcare providers and patients. This study investigates patient satisfaction and its provider-related determinants at Banadir and De Martino hospitals in Mogadishu, Somalia.MethodsA cross-sectional study was conducted from May to August 2023, involving 384 adult patients (aged 18 years and older) seeking outpatient healthcare services at two public hospitals in Mogadishu, Somalia. Data were collected using structured questionnaires and analyzed using STATA 16 software.ResultsOf the 384 participants, 58.6% were under 30 years of age, and 88% were female. The overall patient satisfaction rate was 53.13%. While 61.98% of patients were unsatisfied with accessibility, but 73.70% were satisfied with the humanness of care. Most participants were married (68.2%) and illiterate (62.2%). Significant associations were found between patient satisfaction and education level (p = 0.009), as well as income (p < 0.001). Other demographic factors did not significantly influence satisfaction levels.DiscussionsThe study found a modest patient satisfaction with public hospitals in Mogadishu. The lowest domain score was for continuity of care, while the highest was for humanness of care. These findings provide crucial baseline data for enhancing service quality and patient-centered care in Somalia's conflict-affected urban healthcare settings.